The Increase in Nutritional Status by Fermented Milk Supplement on Elementary School Children from Fishermans Village in Bantul, Yogyakarta Province of Indonesia - Kesetyaningsih, Tri Wulandari; Orbayinah, Salmah; Suryani, Lilis (Berkala Kedokteran, 2018)
Abstract: Probiotics drinks, containing Lactobacillus, were rapidly developed because of its benefit to the health. The bacteria reduced the pathogenic microorganism growth such as virus, fungi, and protozoa. The nutritional status is influenced by food intake, immunity and infection. The children of fishermanâs village are included in the insecure nutrition group because of the low social economic status and healthy living behavior. The aim of this research was to know the influence of daily consumption of probiotics in fermented milk to the nutrition status in elementary school children. This research is quasi-experimental with pretest-posttest control group design. Subjects of 95 elementary school children were divided into 2 groups: 62 children as treatment group and 33 children as control group. Determination of nutritional status is based on anthropometry according to CDC 2000 (BMI-age) growth-chart; and the biochemistry parameter consist of the level of serum total protein, albumin, blood urea nitrogen (BUN), urine creatinine and hemoglobin. Determination of serum total protein and BUN were carried out by Microkjeldahl method, hemoglobine by cyanmet hemoglobin method, albumin by dye-binding method, and creatinine level by Jaffe reaction method. The infection status was determined by anamnesis and laboratory examination of feces which was conducted to find the parasite in the stool. Of sixty five ml fermented milk, that contains of 6.5 x 109 Lactobacillus shirota strain, was consumed every day in 37 days. The data was analyzed by Wilcoxon test for nonparametric data and paired T-test for parametric data. Â The result shows that after the treatment, it increased the nutritional status athropometrically from underweight to normal (12.9%) and overweight to normal (3.23%). In biochemically, it increased the total protein level from 6,111 to 6,705 mg/dL (p=0,001) and decreased the BUN from 42,709 to 41,127 mg/dL (p=0,004) significantly eventhough it was in normal range. The conclusion is that consuming fermented milk for 37 days in children is proven to enhance the nutritional status both by anthropometric and biochemistry parameter.Â Keywords: probiotic, nutritional status, Lactobacillus, fermented milk supplement